2018
DOI: 10.1002/jcp.27925
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA MALAT1 protects cardiomyocytes from isoproterenol‐induced apoptosis through sponging miR‐558 to enhance ULK1‐mediated protective autophagy

Abstract: Investigating the molecular mechanisms of myocardial infarction (MI) and subsequent heart failure have gained considerable attention worldwide. Long noncoding RNA (lncRNA) metastasis‐associated lung adenocarcinoma transcript 1 (MALAT1) has been previously demonstrated to regulate the proliferation and metastasis of several tumors. However, little is known about the effects of MALAT1 in MI and in regulating the cell date after MI. In our study, first, it was shown that the expression levels of MALAT1 were incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(40 citation statements)
references
References 51 publications
3
37
0
Order By: Relevance
“…Prolonged hypertrophy of cardiomyocytes leads to heart failure . Isoproterenol (ISO) was also found to induce the hypertrophy or mitochondria‐dependent apoptosis of H9C2 cells . MALAT1 protected cardiomyocytes against ISO induced apoptosis and improved the cardiac functions upon via inhibition of miR‐558 .…”
Section: Malat1 and Cardiac Dysfunctionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prolonged hypertrophy of cardiomyocytes leads to heart failure . Isoproterenol (ISO) was also found to induce the hypertrophy or mitochondria‐dependent apoptosis of H9C2 cells . MALAT1 protected cardiomyocytes against ISO induced apoptosis and improved the cardiac functions upon via inhibition of miR‐558 .…”
Section: Malat1 and Cardiac Dysfunctionmentioning
confidence: 99%
“…Isoproterenol (ISO) was also found to induce the hypertrophy or mitochondria‐dependent apoptosis of H9C2 cells . MALAT1 protected cardiomyocytes against ISO induced apoptosis and improved the cardiac functions upon via inhibition of miR‐558 . Consistently, miR‐558 mimic decreased the cell viability and enhanced the apoptosis via inhibition of threonine UNC‐51‐like kinase, which exert protective effect by inducing autophagy …”
Section: Malat1 and Cardiac Dysfunctionmentioning
confidence: 99%
“…Apoptosis and autophagy are two pivotal events of programmed cell death in the pathological mechanisms of AMI injury (Bao et al, 2018). Cardiomyocyte apoptosis and autophagy occur during sustained and severe ischemia, usually involving myocardial pump failure (Guo et al, 2019). Studies have reported that autophagy plays a dual role, an opposite role in heart disease, whereas excessive autophagy resulting from prolonged hypoxia may induce cell death and cardiac dysfunction (Jian et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…miR-21, a miRNA transcribed by RNA polymerase II, is widely expressed in endothelial cells and exerts protective functions after Guo et al, 2019;Huang S. et al, 2019;Sun and Zhang, 2019 DAPK2, death associated protein kinase 2; Drp1, dynamin-related protein-1; KBTBD7, kelch repeat and BTB (POZ) domain containing 7; lncRNA, long non-coding RNA; MI, myocardial infarction; miR, microRNA; MALAT1, metastasis associated lung adenocarcinoma transcript 1; MSC, mesenchymal stem cell; NF-κB, nuclear factor-κB; PTEN, phosphatase and tensin homolog deleted on chromosome 10; TNF-α, tumor necrosis factor-α.…”
Section: Mir-208 and Mir-499mentioning
confidence: 99%
“…It was initially reported that genetic deletion or pharmacological inhibition of MALAT1 reduced vascular growth in vivo, suggesting that MALAT1 promoted angiogenesis in ischemic diseases (Michalik et al, 2014). Besides, it has been shown that MALAT1 protects against cardiomyocyte apoptosis after MI by sponging miR-558, thereby inducing Unc-51-like autophagyactivating kinase 1-dependent protective autophagy (Guo et al, 2019). However, a recent study reported that MALAT1 promoted cardiac fibrosis and deteriorated cardiac function post-MI by increasing TGF-β1 activity and inhibiting miR-145 expression (Huang S. et al, 2019).…”
Section: Long Ncrnas (Lncrnas)mentioning
confidence: 99%